Maternal hypertensive disorders during pregnancy and their link to childhood asthma: a systematic review and meta-analysis - Jia, Yanyun; He, Yajun; Ai, Chuchu; Liu, Yan; Zhang, Kui (Frontiers in Pediatrics, 2025)
ObjectiveThe association between Hypertensive Disorders of Pregnancy (HDP) and childhood asthma remains controversial, with limited systematic synthesis. This study aimed to integrate global observational evidence to evaluate the relationship between HDP [and its subtypes, pre-eclampsia (PE) and gestational hypertension (GH)] and offspring asthma risk, while exploring sources of heterogeneity.MethodsFollowing PRISMA 2020 and MOOSE guidelines, 20 observational studies (n = 9,447,593) were identified via systematic searches in Cochrane Library, PubMed, Web of Science, and ScienceDirect (up to January 2025). Random-effects meta-analysis pooled odds ratios (ORs), with subgroup analyses for HDP subtypes, geographic regions, and offspring age. Quality was assessed using the modified Newcastle-Ottawa Scale (mNOS) for cohorts and AHRQ checklist for cross-sectional studies.ResultsHDP exposure significantly increased childhood asthma risk (pooled OR = 1.20, 95% CI = 1.14–1.26, P < 0.00001). PE was associated with asthma (OR = 1.20, 95% CI = 1.13–1.27), but GH was not (OR = 1.15, 95% CI = 0.99–1.32). Stratified analyses revealed increased risk in European (OR = 1.20) and North American (OR = 1.62) populations, and in infants (0–2 years, OR = 1.27) and school-aged children (7–12 years, OR = 1.22), but not in Asian populations or 2–6-year-olds. Sensitivity analyses confirmed result robustness.ConclusionHDP (particularly PE) exposure is significantly associated with increased offspring asthma risk, with age- and region-specific heterogeneity. Future multicenter cohorts should validate causality and explore subtype-specific mechanisms and interventions for early asthma prevention.Systematic Review RegistrationPROSPERO 2025 CRD420251052620.